Wharton’s Jelly Bioscaffolds Improve Cardiac Repair with Bone Marrow Mononuclear Stem Cells in Rats - Luize Kremer Gamba; Laiza Kremer Gamba; Camila da Costa; Aline Luri Takejima; Rossana Baggio Simeoni; Isabella Cristina Mendes Rossa; Anna Clara Faidiga Silva; Julia Letícia de Bortolo; Marcos Antônio Denk; Seigo Nagashima; Carlos de Almeida Barbosa; Paulo Cesar Lock Silveira; et al. (Journal of Functional Biomaterials)
This study assessed the impact of implanting mononuclear stem cells and Wharton’s Jelly (WJ), either separately or together, on left ventricular dysfunction following myocardial infarction in Wistar rats. Functional and histopathological parameters were analyzed, and a rat model of left anterior descending coronary artery ligation was used. Treatments included an intramyocardial injection of 0.9% sodium chloride (control, n = 14), decellularized WJ (n = 12), bone marrow-derived mononuclear cells (BMMC) (n = 12), and bone marrow-derived mononuclear cells (BMMC) combined with WJ (n = 15). Echocardiography assessed the left ventricular function and ejection fraction over four weeks. Histological and immunohistochemical analyses with anti-factor VIII evaluated angiogenesis and collagen types I and III. The results showed no statistically significant effect on ventricular remodeling 30 days post-acute myocardial infarction (AMI). Moreover, the infarct area was significantly smaller in the BMMC + WJ group compared to the control group, suggesting a potential benefit in reducing myocardial scarring. BMMC + WJ therapy demonstrated potential for functional improvement and infarct size reduction 30 days post-infarction. Further studies are needed to confirm its therapeutic benefits.